Three-dimensional trunk kinematics in golf: between-club differences and relationships to clubhead speed - Joyce, C.; Burnett, A.; Cochrane, J.; Ball, K. (Sports Biomechanics, 2013)
The aims of this study were (i) to determine whether significant three-dimensional (3D) trunk kinematic differences existed between a driver and a five-iron during a golf swing; and (ii) to determine the anthropometric, physiological, and trunk kinematic variables associated with clubhead speed. Trunk range of motion and golf swing kinematic data were collected from 15 low-handicap male golfers (handicap = 2.5 ± 1.9). Data were collected using a 10-camera motion capture system operating at 250 Hz. Data on clubhead speed and ball velocity were collected using a real-time launch monitor. Paired t-tests revealed nine significant (p ? 0.0019) between-club differences for golf swing kinematics, namely trunk and lower trunk flexion/extension and lower trunk axial rotation. Multiple regression analyses explained 33.7-66.7% of the variance in clubhead speed for the driver and five-iron, respectively, with both trunk and lower trunk variables showing associations with clubhead speed. Future studies should consider the role of the upper limbs and modifiable features of the golf club in developing clubhead speed for the driver in particular.